Feasibility of the Omaha system for the care of children with dilated cardiomyopathy - Zhang, Qin; Zhang, Ai; Wang, Yanqin; Lv, Tiewei; Sun, Ping; Zhao, Xiaoxia; Li, Rui; Zheng, Xianlan (Frontiers in Pediatrics, 2023)
Aim: To explore the feasibility of Omaha system theory in the care of children with dilated cardiomyopathy (DCM), which may provide a practical basis for the continuous nursing of DCM children. Methods: A total of 1,392 records describing symptoms, signs, and nursing interventions were extracted from the medical records of 76 children suffered from DCM. Content analysis method was used to find out existent nursing problems, make precise nursing plans, and take corresponding nursing measurements according to the medical records of DCM children. Cross-mapping method was utilized to compare the conceptual consistency of the medical records and Omaha system (problem classification and intervention subsystems). Results: Of the total 1,392 records, 1,094 (78.59%) were complete consistency, while 245 (17.60%) were partial consistency, and 53 (3.81%) were inconsistency with the Omaha system concepts. The concept matching degree of medical records and Omaha system was approximately 96.19%. Conclusions: The Omaha system may be an effective nursing language for Chinese DCM children, which may be useful to guide nurses in the care of DCM. Further well-design studies need to fully evaluate the feasibility and effectiveness of the Omaha system in nursing children with DCM.